2021
DOI: 10.1002/ncp.10662
|View full text |Cite
|
Sign up to set email alerts
|

Oral iron supplementation in patients with chronic kidney disease: Can it be harmful to the gut microbiota?

Abstract: Patients with chronic kidney disease (CKD) have several pathophysiological alterations, including anemia, one of the first changes in CKD patients. More recently, researchers have observed that the intestinal microbiota alterations are also another complication in these patients. The most common treatment for anemia is oral (mainly ferrous sulfate) or intravenous iron supplementation. Despite being a necessary treatment, recent studies have reported that supplementation with oral iron may increase its availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…There was a high risk of death and/or adverse events in patients with hemoglobin levels outside the target range, high-amplitude hemoglobin fluctuations, consistently high serum ferritin levels, and high-amplitude ferritin fluctuations (22). Current studies have also found oral Fe supplementation may adversely affect intestinal microbiome composition, intestinal and systemic metabolites, host immunity, and infection in Fe-deficient CKD patients, although there are many clinical benefits of oral Fe supplementation in patients with CKD, and further studies are needed to clarify the benefits and disadvantages (23,24). Since IV Fe supplementation bypasses the normal physiological process of intestinal Fe absorption, iatrogenic Fe overload may occur, increasing the risk of infection.…”
Section: Fe and Inflammationmentioning
confidence: 99%
“…There was a high risk of death and/or adverse events in patients with hemoglobin levels outside the target range, high-amplitude hemoglobin fluctuations, consistently high serum ferritin levels, and high-amplitude ferritin fluctuations (22). Current studies have also found oral Fe supplementation may adversely affect intestinal microbiome composition, intestinal and systemic metabolites, host immunity, and infection in Fe-deficient CKD patients, although there are many clinical benefits of oral Fe supplementation in patients with CKD, and further studies are needed to clarify the benefits and disadvantages (23,24). Since IV Fe supplementation bypasses the normal physiological process of intestinal Fe absorption, iatrogenic Fe overload may occur, increasing the risk of infection.…”
Section: Fe and Inflammationmentioning
confidence: 99%
“…Although the effect of drugs on the gut microbiota has been studied over the past few years, the impact of the gut microbiota on the metabolism of drugs commonly used for CKD remains untested. Patients with CKD undergo polypharmacy and commonly use many medications, such as antibiotics, iron, and proton pump inhibitor, with a well-documented negative impact on the uremic gut microbiota [ 142 , 143 , 144 , 145 ]. For other drugs, such as phosphate binders and oral adsorbent AST-120, the effects on the gut microbiota are better known.…”
Section: Gut Microbiota Modulation and Effects On Residual Kidney Fun...mentioning
confidence: 99%
“…Newer oral iron agents (ferric maltol, ferric citrate, and sucrosomial iron), which are better tolerated and more effective than traditional iron salts, 55 have not been evaluated in KTRs. However, oral iron may be harmful to the gut microbiota, 56 and recent studies suggest that the host microbiota profile exerts an important effect on the KT outcome. 57 Compared with oral preparations, IV iron has a higher capacity to correct iron parameters and increase Hb levels, with a similar safety profile in patients with CKD treated with dialysis or those with non–dialysis-dependent CKD.…”
Section: Causes Of Posttransplant Anemiamentioning
confidence: 99%